Fisheries Management Practices in Coastal Karnataka: Fishers’ Perception - ADIGA, M. SURESHA; OJHA, S. N.; MISHRA, S. K.; KUMARI, H. V. DIVYA; JAGADEESH, T. D.; MAHESWARA, K. J. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
The opinions of the primary producers are very important for the development of fisheries management measures. In this study, Focus Group Discussion (FGD) method was considered to overcome this gap. It was observed that fishers agreed for banned season mainly because of sea safety and to reduce fishing pressure. They believed that mesh size regulation was not a useful method and it was not followed as it results in poor catch. It was felt that some of the fishers could be nominated by the group to carry out the agreed upon issues which could be monitored and encouraged by Department of Fisheries.